Family Financial Management of Indonesian Workers in Malaysia - Mohamad, Mohaizi bin; Nasor, Nasor; Abdul Wakhid, Ali; Eliza, Any; Nasrudin, Nasrudin (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2025)
Financial management of the families of Indonesian migrant workers is very important because it can affect the financial welfare of the family. This community service activity aims to provide assistance regarding the financial management system for Indonesian families and workers in Malaysia, as well as providing recommendations to improve their welfare and protection. This community service activity uses ABCD (Asset Based Community Development) with stages of preparation, implementation, evaluation and follow-up. The results of community service activities show positive results.  This shows that there was an increase in the average written test score of 27 points from before starting community service. This shows that community service participants have increased knowledge and skills regarding an effective and efficient family financial management system. They are able to answer questions related to the material presented in community service correctly and quickly.  In conclusion, community service regarding an effective and efficient family financial management system was successfully implemented by 35 Indonesian workers working in Malaysia. Community service participants have increased knowledge, skills, attitudes and motivation towards the family financial management system. Community service participants are able to prepare and implement family budget and savings plans according to their income and needs.